2021
DOI: 10.3390/ijms222010940
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Intervention Mitigates Pathological Liver Changes in NAFLD Zebrafish by Activating SIRT1/AMPK/NRF2 Signaling

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a common disease that causes serious liver damage. Exercise is recognized as a non-pharmacological tool to improve the pathology of NAFLD. However, the antioxidative effects and mechanisms by which exercise ameliorates NAFLD remain unclear. The present study conducted exercise training on zebrafish during a 12-week high-fat feeding period to study the antioxidant effect of exercise on the liver. We found that swimming exercise decreased lipid accumulation and improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 83 publications
(102 reference statements)
1
25
0
Order By: Relevance
“…Our study results showed that moderate-intensity CT for eight weeks reduced doxorubicin-induced hepatocyte apoptosis in male rats. In line with the findings of our study, Zou et al (17) performing the TUNEL assay also found that 12 weeks of endurance swimming training reduced apoptosis in hepatocytes of zebrafish with nonalcoholic fatty liver disease (NAFLD). Alihemmati et al (18) demonstrated that interval aerobic training mitigated pre-apoptotic indices of Bax/Bcl2 ratio and Bax levels and caspase-6 while increasing Bcl2 levels.…”
Section: Discussionsupporting
confidence: 92%
“…Our study results showed that moderate-intensity CT for eight weeks reduced doxorubicin-induced hepatocyte apoptosis in male rats. In line with the findings of our study, Zou et al (17) performing the TUNEL assay also found that 12 weeks of endurance swimming training reduced apoptosis in hepatocytes of zebrafish with nonalcoholic fatty liver disease (NAFLD). Alihemmati et al (18) demonstrated that interval aerobic training mitigated pre-apoptotic indices of Bax/Bcl2 ratio and Bax levels and caspase-6 while increasing Bcl2 levels.…”
Section: Discussionsupporting
confidence: 92%
“…Exercise reduced NAFLD damage caused by HFD by inhibiting lipolysis and enhancing mitochondrial biosynthesis and fatty acid oxidation, and these changes are the result of activation of cellular pathways mediated through Sirt1 [ 34 ]. In the constructed zebrafish model of NAFLD, swimming exercise improved hepatic steatosis, inflammation, fibrosis and so on caused by HFD, and these beneficial effects were related to activated Sirt1 signaling [ 35 ]. In addition, exercise also alleviates the progression of many diseases by upregulating Sirt1, such as inflammation and metabolic dysfunction of the liver and kidney caused by diabetes [ 36 ], myocardial ischemia/reperfusion injury [ 37 ] and hypothalamic inflammation [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of MET and/or exercise on hepatocyte apoptosis could be partly attributed to the activation role of AMPK and related antiapoptotic signaling pathways. Recently, Zou et al reported that the underlying mechanisms of alleviating the pathological changes in livers induced by high-fat diets through exercise may be related to SIRT1/AMPK signaling pathways [55]. Zhao et al also showed the important role of an AMPK-caspase-6 axis in regulating liver damage in NASH [56].…”
Section: Discussionmentioning
confidence: 99%